2017
DOI: 10.1177/1464884917731180
|View full text |Cite
|
Sign up to set email alerts
|

Is business news starting to bark? How business news covers corporate social responsibility post the economic crisis

Abstract: This study seeks to give a timely perspective on understanding how business news covers corporate social responsibility in light of heavy criticism financial journalists have faced since the latest economic depression in the United States. Building upon previous research and using agenda setting, framing, and agenda building as a theoretical base, a content analysis was conducted to examine how business news portrays corporate social responsibility and the tone used in coverage both before and after the econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…There is a possibility that some of the CSR promotions were “surreptitious advertisement” (Tang, 2012, p. 282), which contributes to the dominant positive tone in the media coverage of CSR. Consistent with previous findings (Furey et al , 2019), this study also found that business newspapers were more likely to adopt a positive tone when covering CSR issues, as compared to the mainstream newspapers. A large amount of CSR-related news in business media indicates close connections between business journalists and corporate sources (Davis, 2000).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…There is a possibility that some of the CSR promotions were “surreptitious advertisement” (Tang, 2012, p. 282), which contributes to the dominant positive tone in the media coverage of CSR. Consistent with previous findings (Furey et al , 2019), this study also found that business newspapers were more likely to adopt a positive tone when covering CSR issues, as compared to the mainstream newspapers. A large amount of CSR-related news in business media indicates close connections between business journalists and corporate sources (Davis, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, it seemed that CSR was portrayed in a positive way regardless of the geographical variances. Our sample consisted of both business sections (Furey et al , 2019) and other news sections covering CSR issues, such as letters and news stories promoting companies’ CSR achievements and interviews featuring companies’ CSR performances. There is a possibility that some of the CSR promotions were “surreptitious advertisement” (Tang, 2012, p. 282), which contributes to the dominant positive tone in the media coverage of CSR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, previous research has confirmed the media's watchdog role for economic news (Kalogeropoulos et al, 2015). Similarly, Furey et al (2019) found that the media coverage of CSR has become less positive after the financial crisis. Although the criticism in the aftermath of the financial crisis was mainly levelled against journalists, this could have impacted the other news producers as well, since their audiences might have become more suspicious of positive tone, too.…”
Section: Tone Before and After The Financial Crisismentioning
confidence: 91%
“…In the new media environment, however, some have questioned the agenda-setting role (Bennett and Iyengar, 2008;Furey et al, 2017;Meraz, 2011;Vonbun et al, 2016). The argument is that in the current fragmented and polarized media context, a shared and homogeneous agenda, which is the basic assumption of agenda-setting theory, no longer exists, especially for attributes of issues or objects.…”
Section: Agenda-setting Effects and How They Workmentioning
confidence: 99%